(untitled) (Fiep Bulletin - online, 2014)
Initiation sports and careers of footballers are currently too topics discussed. The ways to select these athletes, the ideal age to start training, pedagogy proper posture coach, are some of the issues further discussion. What are the main aspects related to each transition of the sporting career of those players. There is a relationship between the current structure of professional football, which puts the athlete in a tight labor market, and the practices of freedom as a way of positioning the athletes on the structure at the same time, validate and manage their careers. How to discuss the Modern Sport and the control that the International Football Federation (FIFA) has on professional football and movement of footballers dreaming in search of football markets abroad. The methodological approach applied was to review the literature and expository articles indexed by the chosen descriptors: sports initiation, football and athletic career. Large numbers of football players have not had experience with other methods when very migrate from futsal to football or vice versa. One feature of the transition from amateur to professional is that it is a function of the level of athletic performance and if it is not selected, the individual may be forced to stop playing. The motivation depends on the source expiradora. Sad reality: in Brazil, 82 % of football players receive up to two minimum wages. The competition requires athletes’ dedication and uniqueness. Most individuals, former professional football players, exert a profession football related, as technicians, technical experts and commentators. Thus, this research concludes that the process of initiation and athletic career in football occurs in ages and so debatable, featuring early specialization and consequent abandonment.